Matrix-Induced Autologous Chondrycte Implantation for a Glenoid Chondral Defect: A Case Report. Issue 2 (April 2020) - Steinmetz, Garrett; Hamilton, John; Fernandes, Carl; Bond, James
Abstract : Case: We describe the case of a 33-year-old man who had a 1.5 × 2 cm chondral defect of the right glenoid that that was discovered on arthroscopy and was successfully treated with matrix-induced autologous chondrocyte implantation (MACI). At 2 years postoperatively, the patient's Constant score and American Shoulder and Elbow Surgeons (ASES) shoulder score improved by 44 and 51.6 points, respectively. Conclusion: Chondral lesions of the glenoid are rare and are a challenge to manage. This case represents a successful outcome with MACI, thus providing surgeons with an option for treating these difficult problems.